Analysis of Non-Penal Settlement of Traffic Crime Cases in a Progressive Law Perspective (Research Study at the Pati City Police Resort) - Darmawan, Moch Satria; Supoyono, Eko (Jurnal Hukum Khaira Ummah, 2025)
Traffic crimes such as traffic accidents have been ignored against the legal provisions stipulated in the traffic and road transportation laws, in practice quite a lot of police choose not to continue the case process and prefer to resolve it through deliberation between the victim and the perpetrator. In the current legal situation, if we still apply the legal-positivism understanding which views the law as limited to regulations alone, what happens is that the law serves certain interests, not substantive justice and the people at large, so that the purpose of the law to realize justice is increasingly far from what is expected. The aim of this research is to identify and analyze (1) the instruments of criminal provisions in the scope of traffic crimes, (2) the mechanisms for implementing the settlement of traffic criminal cases through non-penal channels, (3) the problems for law enforcers in implementing the settlement of traffic criminal cases through non-penal channels. The approach method used in this study is sociological juridical. The specifications of this study are descriptive analytical. The data sources used are primary data and secondary data. Primary data is data obtained directly from the field or from the first source and has not been processed by other parties. While secondary data is obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research and discussion, it can be concluded: (1) Based on Law Number 22 of 2009 for each specific road traffic violation, road traffic violations are classified into three types of violations, namely minor traffic violations; moderate traffic violations; and serious traffic violations. The division of classifications based on the type of violation is basically used as a benchmark for determining the amount of fines and imprisonment or imprisonment. (2) In the event that the parties are ready to meet, the police will explain the results of their findings related to the results of the crime scene investigation and statements from witnesses, after both parties understand and accept the results of the explanation, then based on their discretionary authority the police will give the parties the freedom to determine the settlement process for the case by means of deliberation or through the applicable legal process. (3) In terms of legal problems, there is no institution that supervises the results of the settlement of non-penal criminal cases with the concept of implementing restorative justice so that the perpetrators are negligent in carrying out their obligations.